Automated Model Verification using an Equivalence Test on a Reference Mode - Akbulut, Akin; Abke, Stephan; Laroque, Christoph (Proceedings of the 2017 Winter Simulation Conference)

Using Sentiment Analysis on Local Up-to-the-Minute News: An Integrated Approach - Kersting, Joschka; Geierhos, Michaela (Proceedings of the 23rd International Conference on Information and Software Technologies, Communications in Computer and Information Science)

Automatisierte Modellverifikation mithilfe einer Äquivalenzprüfung an einem Referenzmodell - Akbulut, Akin; Laroque, Christoph; Dangelmaier, Wilhelm

From User Demand to Software Service: Using Machine Learning to Automate the Requirements Specification Process - van Rooijen, Lorijn; Baeumer, Frederik Simon; Platenius, Marie Christin; Geierhos,, Michaela; Hamann, Heiko; Engels, Gregor

Guesswork? Resolving Vagueness in User-Generated Software Requirements - Geierhos, Michaela; Baeumer , Frederik Simon (Partiality and Underspecification in Information, Languages, and Knowledge)

Studying Software Descriptions in SourceForge and App Stores for a better Understanding of real-life Requirements - Baeumer, Frederik Simon; Markus, Dollmann (Proceedings of the 2nd ACM SIGSOFT International Workshop on App Market Analytics)

Studying Software Descriptions in SourceForge and App Stores for a better Understanding of real-life Requirements - Baeumer, Frederik Simon; Dollmann, Markus; Geierhos, Michaela (Proceedings of the 2nd ACM SIGSOFT International Workshop on App Market Analytics)

Production theory 1 - Dangelmaier, Wilhelm
n the multi-volume work on "Theory of Production", the production models and processes born today from practice are to be derived for the first time on a mathematically justified basis and thus also given the production economy a scientific basis. A constructivist point of view is to be set aside for “we just organized our company that way and it has proven itself”, and so the many descriptive “factory management teachings” are to be replaced. Volume 1 contains the basics of logic, set theory and algebra. The production-relevant conceptions of systems theory are for the first time completely mapped to constructs of formal logic, propositional and predicate logic consistently presented using examples. The predicate logic strikes the bow to the NC program; all parameters of a machining production are derived explicitly. An application example of the set-theoretical concepts is the computer-aided design, the relational calculus is mapped, for example, to product structures, replacement parts and identical parts. The basics of algebra deal in detail with the algebraic systems with internal connections that are important for engineering. Rotating tool magazines are mentioned here as an example. Algebraic systems with external links deal in particular with the handling of matrices. The basics of classifying, ordering and measuring conclude this volume. The basics of algebra deal in detail with the algebraic systems with internal connections that are important for engineering. Rotating tool magazines are mentioned here as an example. Algebraic systems with external links deal in particular with the handling of matrices. The basics of classifying, ordering and measuring complete this volume. The basics of algebra deal in detail with the algebraic systems with internal connections that are important for engineering. Rotating tool magazines are mentioned here as an example. Algebraic systems with external links deal in particular with the handling of matrices. The basics of classifying, ordering and measuring conclude this volume.

Production theory 2 - Dangelmaier, Wilhelm
In the multi-volume work on "Theory of Production", the production models and processes born today from practice are to be derived for the first time on a mathematically justified basis and thus also given the production economy a scientific basis. A constructivist point of view is to be set aside for “we just organized our company that way and it has proven itself”, and so the many descriptive “factory management teachings” are to be replaced. Volume 2 deals with the structures of production. Based on the newly interpreted construct of the “production point”, larger units are composed step by step: single-stage and multi-stage technical quantities. In addition, the production point integrates the subdivision used today in business administration into the object-oriented, activity favoring black box thinking and the functionalist view of consumption and production functions. The conceptual foundations are mainly algebraic input-output systems. Based on the structuring and parameterization options at the production point, alternative organizational concepts for single and multi-level productions are developed. For the engineering sciences, a detailed treatise on the evaluation of production success is particularly important in this volume, which systematically leads to product calculation and the planning of an economically successful production program. Based on the structuring and parameterization options at the production point, alternative organizational concepts for single and multi-level productions are developed. Particularly important for the engineering sciences is a detailed treatise in this volume on the evaluation of production success, which systematically leads to product calculation and the planning of an economically successful production program. Based on the structuring and parameterization options at the production point, alternative organizational concepts for single and multi-level productions are developed. For the engineering sciences, a detailed treatise on the evaluation of production success is particularly important in this volume, which systematically leads to product calculation and the planning of an economically successful production program.

Production theory 3 - Dangelmaier, Wilhelm
In the multi-volume work on "Theory of Production", the production models and processes born today from practice are to be derived for the first time on a mathematically justified basis and thus also given the production economy a scientific basis. A constructivist point of view is to be set aside for “we just organized our company that way and it has proven itself”, and so the many descriptive “factory management teachings” are to be replaced. Volume 3 deals with production processes in time. Ordinal and cardinal amounts of time lead to the system-theoretical definition of a process at the point of production and the possible understandings of processes and states. A main point here is the derivation of the common thinking in series production in terms of performance figures. Starting from the basic form of a time-based production, efficient dynamic events and processes are prepared. This creates the basis for the representation of the state of a general time system and the use of sequential machines. Time-invariant time systems and stochastic productions are the basis of robust production. The point of production and the time system find an ideal symbiosis in the use of finite automatons: A finite number of states together with a limited amount of inputs leads to state-driven production - one of the essential prerequisites for the realization of Industry 4.0. This creates the basis for the representation of the state of a general time system and the use of sequential machines. Time-invariant time systems and stochastic productions are the basis of robust production. The point of production and the time system find an ideal symbiosis in the use of finite automatons: A finite number of states together with a limited amount of inputs leads to state-driven production - one of the essential prerequisites for the realization of Industry 4.0. This creates the basis for the representation of the state of a general time system and the use of sequential machines. Time-invariant time systems and stochastic productions are the basis of robust production. The point of production and the time system find an ideal symbiosis in the use of finite automata: A finite number of states together with a limited number of inputs leads to state-driven production - one of the essential prerequisites for the realization of Industry 4.0.

Effektives Customer Relationship Management - Helmke, Stefan; Uebel, Matthias; Dangelmaier, Wilhelm

Setup Optimization Based on Virtual Tooling for Manufacturing in Order to Provide an Intelligent Work Preparation Process - Weber, Jens; Reisch, Raphael-Elias; Schr{\, Christian; Laroque, Christoph

A Multi-User-Collaboration Platform Concept for Managing Simulation-Based Optimization of Virtual Tooling as Big Data Exchange Service - Weber, Jens

Theoretical Concept of Inverse Kinematic Models to determine valid Work Areas using Target Coordinates from NC-programs - Weber, Jens

Sentiment analysis - Geierhos, Michaela (Encyclopedia {\ "a} the business informatics)

Webmonitoring - Geierhos, Michaela (Encyclopedia {\ "a} the business informatics)

On- and Off-Topic Classification and Semantic Annotation of User-Generated Software Requirements - Dollmann, Markus; Geierhos, Michaela (Proceedings of the 2016 Conference on Empirical Methods in Natural Language Processing)

Crawler (focused / not focused) - Geierhos, Michaela (Encyclopedia {\ "a} the business informatics)

Text Mining - Geierhos, Michaela (Encyclopedia {\ "a} the business informatics)

Running Out of Words: How Similar User Stories Can Help to Elaborate Individual Natural Language Requirement Descriptions - Baeumer, Frederik Simon; Geierhos, Michaela (Proceedings of the 22nd Conference on Information and Software Technologies (ICIST 2016))

Time models for the classification and identification of production events - Dangelmaier, Wilhelm (Megatrend digitization - potentials of work and company organization)

How to Complete Customer Requirements Using Concept Expansion for Requirement Refinement - Geierhos, Michaela; Baeumer, Frederik Simon (Proceedings of the 21st International Conference on Applications of Natural Language to Information Systems (NLDB 2016))

Wie verhalten sich Aktionäre bei Unternehmenszusammenschlüssen? Modellierung sprachlicher Muster zur Analyse treibender Faktoren bei der Berichterstattung - Stotz, Sophia Charlotte; Geierhos, Michaela (DHd 2016: Modellierung - Vernetzung - Visualisierung. Die Digital Humanities als fächerübergreifendes Forschungsparadigma. Konferenzabstracts)

Ein Verfahren zur simulationsgestützten Optimierung von Einrichtungsparametern an Werkzeugmaschinen in Cloud-Umgebungen - Laroque, Christoph; Weber, Jens; Reisch, Raphael-Elias; Schröder, Christian (Nissen, Volker;Stelzer, Dirk;Straßburger, Steffen;Fischer, Daniel (Hrsg.): Multikonferenz Wirtschaftsinformatik (MKWI) 2016)

Multi-criteria scheduling and control in dynamic and stochastic environments: A contribution to the creation of robust schedules for freight handling in air freight terminals - Boxnick, Simon

Intelligent work preparation in the cloud - Rehage, Gerald; Isenberg, Florian; Reisch, Raphael-Elias; Weber, Jens; Jurke, Benjamin; Pruschek, Peter (wt workshop technology online)

A Metric for Candidate Selection for a Robust Opportunistic Container Routing in high Complex Distribution Centers - Kopecki, Lukas

A Technical Approach of a Simulation-Based Optimization Platform for Setup-Preparation via Virtual Tooling by Testing the Optimization of Zero Point Positions in CNC-Applications - Weber, Jens (Proceedings of the 2015 Winter Simulation Conference)

A Comparison of the Usage of Different Approaches for the Management of Plant Engineering Projects - Akbulut, Akin; Laroque, Christoph; Wenzel, Sigrid; Jessen, Ulrich (Proceedings of the 2015 Winter Simulation Conference)
Customized planning, engineering and construction of one-of-a-kind products (like wind energy, biogas or power plants) are complex and contain a lot of risks and temporal uncertainties, e.g. of logistics and project schedules. Therefore the management of this kind of projects has to be supported by adequate methods for the estimation of project risks and uncertainties. Based on the results of the joint research project simject of the Universities of Paderborn and Kassel, which aims at the development of a demonstrator for simulation-based and logistic-integrated project planning and scheduling, this paper discusses the usage of different approaches for supporting project management of plant engineering projects. After a short introduction and description of the approaches to be compared a wind energy plant as evaluation model as well as the application of the different methods are presented. Additionally, the usage of the approaches is compared and the advantages and disadvantages are pointed out.

A Deadlock-Free Route Reservation Method for Automatized Decentralized Controlled Transportation in High Complex Distribution Centers - Kopecki, Lukas

A Robust Opportunistic Routing for High complex Decentralized controlled Distribution Center - Kopecki, Lukas

Implementation and Comparison of Cluster-Based PSO Extensions in Hybrid Settings with Efficient Approximation - Mueß, André; Weber, Jens; Reisch, Raphael-Elias; Jurke, Benjamin (Proceedings of the First Conference of Machine Learning for Cyber Physical Systems)

Protocol Structure for Controlling Adaptive Conveyor System in Automatized High Complex Distribution Centers - Kopecki, Lukas

A System for Uncovering Latent Connectivity of Health Care Providers in Online Reviews - Baeumer, Frederik Simon; Geierhos, Michaela; Schulze, Sabine (Information and Software Technologies: 21th International Conference, ICIST 2015, Druskininkai, Lithuania, October 15-16, 2015, Proceedings)

Find a Physician by Matching Medical Needs described in your Own Words - Baeumer, Frederik Simon; Dollmann, Markus; Geierhos, Michaela

An approach for deadlock Prevention in decentralized controlled pre-storage zones with dynamic behavior and time windows - Kopecki, Lukas (International Journal of Materials, Mechanics and Manufacturing)

Der zufriedene Patient 2.0: Analyse anonymer Arztbewertungen im Web 2.0. - Geierhos, Michaela; Schulze, Sabine; Baeumer, Frederik Simon (Working Papers des KVF NRW)

Online-Optimierung zur Festlegung von Bestellzeitpunkten in der Losgrößenfertigung - Dangelmaier, Wilhelm (Schenk, Michael;Zadek, Hartmut;Müller, Gerhard;Richter, Klaus;Seidel, Holger (Hrsg.): 20. Magdeburger Logistiktage "Sichere und nachhaltige Logistik")

Filtering Reviews by Random Individual Error - Geierhos, Michaela; Baeumer, Frederik Simon; Sabine, Schulze; Valentina, Stuß (Current Approaches in Applied Artificial Intelligence, Lecture Notes in Computer Science)

I grade what I get but write what I think." Inconsistency Analysis in Patients‘ Reviews - Geierhos, Michaela; Baeumer, Frederik Simon; Schulze, Sabine; Stuß, Valentina (ECIS 2015 Completed Research Papers)

Hardware in the Loop Framework for decentralized autonomous conveyor in automatic pre-storage zones - Kopecki, Lukas

Asynchronous Optimization Techniques for Distributed Computing Applications - Reisch, Raphael-Elias; Weber, Jens; Laroque, Christoph; Schröder, Christian (Proceedings of the 2015 Spring Simulation Multi-Conference)

Analyzing Supply Chain Nodes in Heterogeneous Environments Based on Transaction Data with Respect to Independent Item Behavior - Lauck, Sebastian; Boxnick, Simon; Kopecki, Lukas (International Journal of Advances in Computer Science & Its Applications - IJCSIA)

Online optimization to determine order times - Dangelmaier, Wilhelm, Wilhelm

Identifikation kognitiver Effekte in Online-Bewertungen - Geierhos, Michaela; Stuß, Valentina

Second-hand experience reports: Findings {\ "about the authorship of doctor reviews in online portals - Geierhos, Michaela; Baeumer, Frederik Simon

What did you mean? Facing the Challenges of User-generated Software Requirements - Geierhos, Michaela; Schulze, Sabine; Baeumer, Frederik Simon (Proceedings of the 7th International Conference on Agents and Artificial Intelligence)

Analytical derivation of the sequence rules for the equalization of high-volume job features - Markwart, Paul

Prescriptive Analytics for Planning Research-Performance Strategy - Minhee, Cho; Weber, Jens; Song, Sa-kwang; Jung, Hanmin; Lee, Mikyoung (Computer Science and Its Applications - Ubiquitous Information Technologies)

Interpersonal relations in biographical dictionaries. A case study - Stotz, Sophia Charlotte; Stuß, Valentina; Reinert, Matthias; Schrott, Maximilian (Proceedings of the First Conference on Biographical Data in a Digital World)